Sharia Banking Performance in Makassar - Salmah Said (Al-Ulum, 2015)
This study aims to analyze the performance of Islamic banking in Makassar. Data collected using questionnaires which was distributed to seven Islamic banks. Supporting data obtained from Bank Indonesia, representatives Makassar and Bank Indonesia’s website. Data then were analyzed using financial ratios, particularly Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR). The results showed that NPF was 1.49% and FDR reached 201.67%. The first ratio indicates low financing problems, while the second shows a high ratio financing provided to society. Furthermore, Islamic principles applied in the system, mechanism, and products offered by the Islamic banking is such a value-added for the societies, which is not found in the conventional ones. The high financial performance of Islamic banking outperforms its counterparts shows significant potential to grow rapidly in the future.